Komunikasi Bisnis Barang Bekas di Media Sosial Instagram - Naufal Ikhsan Nurrokhman; Yulianti (UNISBA Press, 2024)
Abstract. Social media is used as a tool to provide information and as time goes by, many Indonesians are using social media, one of which is the Instagram application. The Instagram application is currently very popular and popular among all levels of society. The online shop @beezweakz uses Instagram as a medium. The phenomenon of online shops that use Instagram, namely Beezweakz, which has an Instagram social media account called @beezweakz, is a company from Bandung that operates in the used goods sector and uses Instagram social media as a business tool. The purpose of this research is to find out how to use social media fonts as a marketing tool by @beezweakz. To find out about content packaging created by @beezweakz. To find out why @beezweakz uses old school bands in their Instagram social media profiles. The researcher used a qualitative method with a case study approach, that is, he wanted to explore information in depth, especially the use of Instagram as a promotional medium. The data collection techniques used in this research used interviews, observation, literature study and documentation. The results of this research show that this font writing strategy is a good step in trying to position the brand in the eyes and minds of buyers, and differentiate used goods from competitors with the aim of providing more value to customers. The concept implemented by @beezweakz is in the form of an old school band in a profile to attract buyers, withstand competitive pressure, and improve its position in the market packaged with visual design. Abstrak. Media sosial digunakan sebagai alat untuk memberikan informasi dan seiring dengan perkembangan zaman, sudah banyak orang Indonesia yang menggunakan media sosial, salah satunya adalah aplikasi instagram. Aplikasi instagram saat ini sedang banyak digemari dan popular di seluruh kalangan masyarakat. Toko online @beezweakz memanfaatkan instagram sebagai media. Fenomena toko online yang menggunakan instagram yaitu Beezweakz yang memiliki akun media sosial instagram bernama @beezweakz merupakan perusahaan asal Bandung yang bergerak di bidang barang bekas dan menggunakan media sosial instagram sebagai sarana bisnis. Tujuan penelitian ini yaitu, untuk mengetahui memanfaatkan tulisan font sosial media sebagai alat pemasaran oleh @beezweakz. Untuk mengetahui pengemasan konten yang dibuat oleh @beezweakz. Untuk mengetahui mengapa @beezweakz menggunakan band jadul dalam profil media sosial instagram. Peneliti menggunakan metode kualitatif dengan pendekatan studi kasus, yaitu itu ingin menggali informasi secara mendalam khususnya pemanfaatan di instagram sebagai media promosi. Teknik pengumpulan data yang dilakukan dalam penelitian ini menggunakan wawancara, observasi, studi kepustakaan dan dokumentasi. Hasil dari penelitian ini didapatkan bahwa Strategi tulisan font ini menjadi langkah yang baik berusaha untuk memposisikan brand di mata dan pikiran pembeli, dan membedakan barang bekas dari pesaing dengan tujuan untuk memberikan nilai lebih bagi pelanggan. Konsep yang dilakukan @beezweakz berupa band jadul dalam profil untuk menarik pembeli, menahan tekanan persaingan, dan memperbaiki posisinya di pasar yang dikemas dengan design visual.